Extended OCL for Goal Monitoring - Robinson, William (Electronic Communications of the EASST, 2007)
Monitoring human-computer interaction aids the analysis for understanding how well software meets its purpose. In particular, monitoring human-computer interactions with respect to a user’s goal model helps to determine user satisfaction. By formalizing a goal model, runtime monitors can be automatically derived. The REQMON system monitors the satisfaction of goal models. Recently, an OCL compiler was developed for REQMON. The OCL was extended slightly to address temporal and real-time constraints. Now, goal models can be represented in the extended OCL, from which runtime monitors can be compiled. The resulting REQMON system appears to be easier to use comes the abstract.